Extracorporeal membrane oxygenation for interstitial lung disease: what is on the other side of the bridge? - Rozencwajg, Sacha; Schmidt, Matthieu (Journal of Thoracic Disease, 2016)
Patients suffering from interstitial lung disease (ILD) share a number of similarities with chronic obstructive pulmonary disease (COPD) patients. The natural evolution in both patient groups is a slow deterioration of lung capacity punctuated by exacerbations, and available treatments are mostly aimed at sustaining lung capacity and preventing exacerbations. Additionally, the last treatment option is lung transplantation (LTx), which is usually performed, in chronic, stable patients. However, management discrepancies are noted between the two patient groups regarding intensive care unit (ICU) admission policy.